Advanced health assessment and clinical diagnosis in primary care - Dains, Joyce E.; Linda Ciofu Baumann;Pamela Scheibel (Saint Louis, Missouri : Elsevier Mosby, 2012)
Designed for advanced practice nurses and advanced practice nursing students, as well as Physician's Assistant students and practitioners, this title approaches physical examination by focusing on a specific chief complaint rather than a diagnosis of a disease entity.
Part I: An introduction to clinical reasoning -- 1 Clinical reasoning, differential diagnosis, evidence-based practice, and symptom analysis -- Part II: Common symptoms in primary care -- 2 Abdominal pain -- 3 Affective changes -- 4 Amenorrhea -- 5 Breast lumps and nipple discharge -- 6 Breast pain -- 7 Chest pain -- 8 Confusion in older adults -- 9 Constipation -- 10 Cough -- 11 Diarrhea -- 12 Dizziness -- 13 Dyspnea -- 14 Earache -- 15 Fatigue -- 16 Fever -- 17 Genitourinary problems in males -- 18 Headache -- 19 Hoarseness -- 20 Limb pain -- 21 Low back pain (acute) -- 22 Nasal symptoms and sinus congestion -- 23 Palpitations -- 24 Penile discharge -- 25 Rashes and skin lesions -- 26 Rectal pain, itching, and bleeding -- 27 Red eye -- 28 Sleep problems -- 29 Sore throat -- 30 Syncope -- 31 Urinary incontinence -- 32 Urinary problems in females and children -- 33 Vaginal bleeding -- 34 Vaginal discharge and itching -- 35 Vision loss -- 36 Weight loss/gain (unintentional) -- Part III Diagnostic imaging -- 37 The chest x-ray -- 38 The abdominal x-ray.
Includes bibliographical references and index.
Keywords: DIAGNOSIS, DIFFERENTIAL